Model Kolaborasi Berbasis Service Learning dalam Meningkatkan Literasi Anak: Studi Kasus Program Membaca Nyaring di Sekolah Dasar - Faujiah, Ani; Nahuri, Nahuri; Rahmawati, Julia; Mutiara, Mutiara (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2025)
Low reading literacy among primary school students, exacerbated by the dominance of digital entertainment, highlights the need for collaborative and sustainable literacy intervention models. This article aims to examine the effectiveness of a service-learning–based collaborative model in improving children’s literacy through a read-aloud program in primary education. Employing a qualitative case study design, the research was conducted at an Indonesian primary school through structured stages of literacy socialization, guided read-aloud activities, and a read-aloud competition involving teachers, parents, and community stakeholders. The findings indicate improvements in students’ reading motivation, read-aloud skills particularly intonation, articulation, and text comprehension and self-confidence, alongside strengthened stakeholder participation in the school literacy ecosystem. This study contributes by proposing a replicable service-learning–based collaborative literacy model that bridges school–community engagement and provides a practical framework for enhancing primary literacy development in similar educational contexts